Synthesis of PtPb hollow nanoparticles and their application in an electrochemical immunosensor as signal tags for detection of dimethyl phthalate. Issue 71 (2nd August 2015) - Liu, Yixin; Zhang, Sen; Ren, Xiang; Wang, Yaoguang; Yan, Liangguo; Wei, Qin; Du, Bin
<x xml:space="preserve">Abstract</x> Platinum–lead (PtPb) hollow nanoparticles were used as signal tags for the first time to fabricate an electrochemical immunosensor. This was the first example of an electrochemical immunosensor used to detect dimethyl phthalate (DMP).